Penerapan Metode MAUT dalam penerimaan Beasiswa Pendidikan Badan Amil Zakat Nasional (BAZNAS) - Perra Budiarti Rahayu Putri; Anggi Hadi Wijaya; Wahyu Fitri (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Scholarships for State universities and Private Universities must be in accordance with predetermined criteria. So far, BAZNAS is still having difficulties in determining the right recipients of scholarships for students or female students to be awarded, so a method is needed in making decisions that are effective and efficient. Aims to determine the awarding of scholarships to students and students using the Multi Attribute Utility Theory (MAUT) method, so that students and students are eligible to get scholarships. Where the data processed in this study were taken from the South Coast National Amil Zakat Agency (BAZNAS) by taking 21 sample data and 6 criterion data, after that a ranking process was carried out so that a valid alternative was obtained. The results of this study used the Multi Attribute Utility Theory (MAUT) method to rank scholarship recipients. The tests carried out showed an accuracy rate of 85.71% for the correct scholarship recipients, resulting in the right students getting the scholarship. The results of the calculation process with the weight of the criteria that show the ranking of alternative scholarship recipients that are close to the criteria and those that are far from the criteria, these results can be used to make decisions about who is entitled to a scholarship.